Characterization of tin selenide nanoparticle films generating from plasma arc penetration of a temperature-varying field - Hakima A. Abdulla; Nadheer Jassim Mohammed; Aseel Mustafa Abdul Majeed (Institute of Advanced Engineering and Science, 2023)
Using the pulsed laser deposition (PLD) method, tin selenide (SnSe) nanoparticles thin films are created on quartz substrates, which are held at different penetration field temperatures Tp-f (Tp-f is the penetration field temperature to which the plasma arc is exposed) (300, 373, 473, and 573) K. X-ray powder diffraction (XRD) reveals a phase transformation from a hexagonal to an orthorhombic structure. The energy gap, which ranges from 1.748-3.15 eV with direct electronic transmission, is calculated using transmittance spectra. Particle size increases by Tp-f increases. Photoluminescence (PL) intensity and film thickness are inversely proportional to each other. Changing the ratio of the compositions provides an essential strategy for altering a material's melting point as well as its energy gap.